Determination of Alkali and Alkaline-earth Metal Content of Bio-diesel Produced from Palm Oil, Palm Kernel Oil and Neem Seed Oil Feed stocks - Ichu Chigozie B., NwakanmaHenry O., and Agulanna Albert C. , (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
Standards are prescribed for fatty acid methyl esters (FAME) used as biodiesel fuels. For its adequate use, biodiesel must conform to these strict standards. The determination of Na, K, Mg and Ca is part of biodiesel characterization of pure biodiesel B100 or blends with petroleum diesel (B2, B5 and B10). Regulations by means of standard methods such as EN 14108, EN 14109, EN 14538 and ASTM D6751 establish a limit of 5 mg/kg as the maximum allowed concentration for Na plus K or Ca plus Mg. Alkali (Na + K) and alkaline earth (Ca + Mg) metal content of biodiesel samples produced from different feed stocks such as palm, palm kernel and neem seed oils was determined using the direct solvent method and a Buck 210VGP Atomic Absorption Spectrophotometer. The mean concentrations of Na, K, Mg and Ca are 19.1, 5.17, 1.8 and 0.00 mg/kg for palm biodiesel, 49.15, 73.2, 1.56 and 0.24 mg/kg for palm kernel biodiesel and 0.26, 111.3, 1.49 and 0.2 mg/kg for neem seed biodiesel respectively. The concentration for Ca plus Mg in all the biodiesel samples was within the maximum limit of 5 mg/kg. This however is not so for Na plus K as its concentration in all the samples exceeded this limit. Analysis of the fuel properties of the biodiesel produced from these feed stocks agreed closely with ASTM D 6751 .